The Influence of Drill Receive Serve and Drill Defense Training Methods to Improve Lower Passing Ability - Nira Nurfadilah; Mulyana, Nanang (Yayasan Insan Mulia Bima, 2024)
The purpose of this study is to improve volleyball players' ability in lower passing by using exercises for defense and receiving and serving. It was determined from field analysis data that the players were unable to receive serves and attacks from their opponents. This study used an experimental design with a one-group pre-test and post-test using quantitative methodology. The study population consisted of female volleyball extracurricular participants of SMK Negeri 2 Kuningan. Purposive sampling was the technique used for the sample. To measure the lower passing ability, the Brady volleyball test was used. Data was examined using Paired Samples T-Test, Normality Test, and Homogeneity Test. After practicing the receive serve drill and the defense technique drill, the findings showed considerable improvement in the lower passing ability. The data was homogeneous and regularly distributed, and the t-test produced a significant result of 0.000 < 0.05. In conclusion, practicing these techniques can improve your ability to pass the ball lower during volleyball matches. A more in-depth understanding of the long-term effectiveness of this method can be obtained through its application in continuous practice.